Piezoelectricity in self-assembled peptides: a new way towards electricity generation at nanoscale - Slabov, Vladislav (2019)
Self-assembled nanostructured peptides are of great interest nowadays due to their biocompatibility and an array of outstanding functional properties. Among them, strong piezoelectricity combined with low dielectric constant is beneficial for high voltage and power generation at the nanoscale. This Chapter is an overview of the piezoelectric phenomena in self-assembled peptides including effects of the growth conditions, self-assembly, and measurement techniques on their functional response as well as the origin of strong piezoelectricity in this material. The current status of electrical energy harvesting in self-assembled peptides useful for biomedical applications along with the challenges and perspectives for using these piezoelectric biomaterials will be discussed. This chapter is expected to provide a guidance towards future design and application of novel functional self-assembled materials based on nanostructured peptides.